Comparative Effects of Continuous and Interval Aerobic Training on Cellular Respiration Indices (OCR) and ATP Content in Skeletal Muscle of Rats with Type 2 Diabetes - Fanaei, Elham; Eftekhari Gheinani ‌Elham; Banaei Borojeni, Jamshid (Health Nexus, 2026)
Type 2 diabetes impairs skeletal muscle energy metabolism, partly through mitochondrial respiratory dysfunction and reduced ATP-generating capacity. This experimental study compared the effects of continuous and interval aerobic training on cellular respiration indices and ATP content in the gastrocnemius muscle of male Wistar rats with type 2 diabetes. Male Wistar rats were allocated to six groups: healthy control, healthy + continuous training, healthy + interval training, diabetic control, diabetic + continuous training, and diabetic + interval training (n = 8 per group). Type 2 diabetes was induced using a high-fat diet followed by intraperitoneal streptozotocin injection. The exercise interventions were performed for eight weeks. After the intervention, gastrocnemius muscle samples were collected for analysis of mitochondrial respiratory indices, including basal respiration, ATP-linked respiration, maximal respiration, spare respiratory capacity, proton leak, coupling efficiency, and tissue ATP content. Data were analyzed using two-way analysis of variance followed by Tukey post hoc tests. Diabetes reduced mitochondrial respiratory indices, spare respiratory capacity, coupling efficiency, and ATP content. Both aerobic training protocols improved respiratory function and ATP content in diabetic rats. The interval training protocol produced larger improvements than continuous training in maximal respiration, spare respiratory capacity, and ATP content. Eight weeks of aerobic training partially restored diabetes-related impairments in skeletal muscle mitochondrial function. Interval aerobic training appeared to produce stronger respiratory adaptations than continuous training. These findings provide preclinical evidence for the role of exercise intensity structure in mitochondrial adaptation under diabetic conditions.